2022
DOI: 10.1038/s41598-022-06947-5
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the stator protein PomA affect switching of rotational direction in bacterial flagellar motor

Abstract: The flagellar motor rotates bi-directionally in counter-clockwise (CCW) and clockwise (CW) directions. The motor consists of a stator and a rotor. Recent structural studies have revealed that the stator is composed of a pentameric ring of A subunits and a dimer axis of B subunits. Highly conserved charged and neighboring residues of the A subunit interacts with the rotor, generating torque through a gear-like mechanism. The rotational direction is controlled by chemotaxis signaling transmitted to the rotor, wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…This is not surprising in the face of recent results showing that the stators and the rotor function as interlocked gears (Santiveri et al, 2020, Tan et al, 2021. Genetics has also shown that non-functional mutations in rotor proteins are compensated for by suppressors in stator proteins and vice versa (Togashi et al, 1997, Garza et al, 1996, Terashima et al, 2022, Kojima et al, 2011. An important take-home message from this section is that the C ring is not the only player determining rotor bias; the stator complexes, which now include FliL, contribute as well.…”
Section: Flil Positioning and Motor Remodelingmentioning
confidence: 83%
See 1 more Smart Citation
“…This is not surprising in the face of recent results showing that the stators and the rotor function as interlocked gears (Santiveri et al, 2020, Tan et al, 2021. Genetics has also shown that non-functional mutations in rotor proteins are compensated for by suppressors in stator proteins and vice versa (Togashi et al, 1997, Garza et al, 1996, Terashima et al, 2022, Kojima et al, 2011. An important take-home message from this section is that the C ring is not the only player determining rotor bias; the stator complexes, which now include FliL, contribute as well.…”
Section: Flil Positioning and Motor Remodelingmentioning
confidence: 83%
“…A variety of bacteria alter motor behavior during swarming, increasing motor speed and suppressing tumbles by altering motor bias (Partridge et al, 2019, Tian et al, 2021. We refer to both effects as 'motor remodeling'.…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising in the face of recent results showing that the stators and the rotor function as engaged gears (Deme et al, 2020; Santiveri et al, 2020; Tan et al, 2021). Genetics has also shown that nonfunctional mutations in rotor proteins are compensated for by suppressors in stator proteins and vice versa (Garza et al, 1996; Kojima et al, 2011; Terashima et al, 2022; Togashi et al, 1997). An important take‐home message from this section is that the C ring is not the only player determining rotor bias.…”
Section: Discussionmentioning
confidence: 99%
“…The stator complexes are dynamic, moving in an out of the rotor by sensing how much torque is needed to drive the rotor (Lele et al, 2013; Tipping et al, 2013). When drifting in the membrane, ion flow through the stators is shut off by a “plug” contributed by the MotB subunit of the complex, opening only when the stators dock at the rotor, and when MotA engages with FliG in the C ring (Hosking et al, 2006; Kojima et al, 2009; Terashima et al, 2022). Ion flow through the stators changes the charge of FliG residues at the MotA‐FliG interface, producing torque and rotor movement (Berg & Turner, 1993; Zhou et al, 1998).…”
Section: Introductionmentioning
confidence: 99%